Understanding Adolescent Mothers' Narratives of Autonomy in Postnatal Care Decision-Making - Ashri, Rizki Hallifah; Hasan, Aliah Bagus Purwakania (Riwayat: Educational Journal of History and Humanities, 2025)
Adolescent mothers are a group that has high vulnerability in the postpartum period, especially related to limited autonomy in making treatment decisions. Age, economic dependence, and cultural and gender norms often put them in a position of disadvantage. This study aims to understand the narrative of adolescent mothers regarding the experience of autonomy in decision-making in postpartum care. The method used is a qualitative narrative study based on a review of the latest literature on obstetrics, adolescent reproductive health, and decision-making practices in maternal care. The analysis focused on the main themes that emerged from the subjective experiences of adolescent mothers. The results of the study show that there is an ambivalence in adolescent mothers between the desire to be independent and the reality of attachment to family and partner support. Factors that strengthen autonomy include midwife support, the availability of clear health information, and the existence of equal communication with the partner. On the other hand, the dominant obstacles are social stigma, financial limitations, and lack of negotiation space within the family and health services. The conclusion of this study emphasizes the importance of strengthening the role of midwives in creating a participatory, culturally sensitive, and empowerment-oriented care model. The implications of these findings are expected to be the basis for improving the quality of postpartum services that are more responsive to the reproductive needs and rights of adolescent mothers.